Quality investing in CEE emerging markets - Zaremba, Adam (Business, Management and Economics Engineering, 2014)
Using sorting, cross-sectional tests, regression, and tests of a monotonic relation, the study examines the return patterns related to seven distinct quality characteristics: accruals, bid-ask spread, balance sheet liquidity, profitability, leverage, payout ratio and turnover. The investigation of more than 1.300 stocks from 11 Central and Eastern European countries for the period 2002–2014 documents a strong gross-profitability premium and an inverted liquidity premium. Profitable and not heavily leveraged companies provide a partial hedge against market distress. Finally, the paper proposes quality spreads as a forecasting tool and shows that they have predictive abilities over quality premiums related to leverage, profitability and bid-ask spread.